Health Impact and Cost-Effectiveness of Sugar-Sweetened Beverage Taxes for Reducing Cancer Burden in the United States (P22-010-19). (13th June 2019) - Griecci, Christina; Du, Mengxi; Kim, David; Eom, Heesun; Ruan, Mengyuan; Cudhea, Frederick; Wong, John; Wilde, Parke; Rehm, Colin; Michaud, Dominique; Lee, Yujin; Micha, Renata; et al.
Abstract: Objectives: Sugar sweetened beverage (SSB) intake is pervasive in the U.S. and a critical risk factor for weight gain and obesity. Obesity is a preventable factor associated with 13 types of cancers. While SSB taxes can lower SSB intake, the potential impact on cancer outcomes, health costs, and cost-effectiveness in the U.S. is lacking. We aimed to evaluate the health outcomes, costs, and cost-effectiveness of a national SSB tax policy for reducing obesity-related cancer in the U.S. Methods: We used the Diet Cancer Outcome Model (DiCOM), a probabilistic cohort state-transition model, to project the effect of a national 0.01 per oz SSB excise tax on 13 obesity-associated cancers among U.S. adults age 20+ years over their lifetime. Model inputs included national demographic and dietary data from the National Health and Nutrition Examination Survey (NHANES) 2013–2016, policy effects, diet-BMI effects, and BMI-cancer effects from meta-analyses, and policy and cancer costs from established sources. Cost-effectiveness was evaluated as net costs with 3% annual discounting, under both government affordability and societal perspectives. Probabilistic sensitivity analyses jointly incorporated uncertainty in model inputs using 1000 simulations. Results: The SSB tax policy was estimated to prevent 20, 545 (95% uncertainty interval [UI]: 12, 586 to 32, 000) new cancers cases and 10, 181 (6362 to 16, 000) cancer deaths and add 67, 100 (41, 100 to 104, 505) quality-adjusted life years (QALYs) over lifetime. Largest health benefits were seen for endometrial, kidney, and liver cancer. The SSB tax was estimated to generate 1.17 billion industry compliance costs, 1.20 billion in government implementation costs, and 5.4 billion in lifetime medical savings for the 13 types of cancer. The SSB tax was net cost saving from a societal perspective and government affordability perspective, at 3.2 billion (95% UI: 2.4 to 4.1) and 4.1 billion (95% UI: 3.4 to 4.9), respectively, not including the 6.6 billion generated from tax revenues. Conclusions: Our modeling estimates that a national 0.01 per oz SSB tax would reduce obesity associated cancer cases and deaths among U.S. adults, and be cost savings from both a societal perspective and government affordability perspective. Funding Sources: NIH/NIMHD. Supporting Tables, Images and/or Graphs: